Investigating teachers' experience and self-efficacy beliefs across gender in implementing the new standards-based curriculum in Ghana - Agormedah, Edmond Kwesi; Ankomah, Francis; Frimpong, James Boadu; Quansah, Frank; Srem-Sai, Medina; Hagan, John Elvis; Schack, Thomas (Frontiers in Education, 2022)
The introduction of the New Standard-based Curriculum in Ghana required teachers to make adjustments, including teaching routines. Despite the challenges encountered in the introduction of this curriculum, its passage was successful. Previous studies have revealed mixed reactions from teachers and how their experiences affect their efficacy during the implementation stage. This study examined whether teachers’ experience and self-efficacy beliefs influenced the implementation of the new curriculum reforms across gender in Ghana. Through cluster sampling technique, 693 basic school teachers were surveyed to respond to the questionnaire. Preliminary assessment showed that teachers exhibited moderate to high level of teaching efficacy in student engagement, instructional strategy, and classroom management. Further, the study also revealed that teaching experience was positively related to efficacy. However, gender significantly moderated the relationship between teaching experience and teachers’ efficacy in student engagement as well as teaching experience and efficacy in student engagement. Findings imply that even though teachers may be more likely to plan and deliver pedagogical contents and carry out instructional activities, their sense of efficacy in managing their classroom is questionable. Emphasizing on teaching experience in improving their efficacy in curriculum implementation is key, especially among female teachers. Programs or capacity building training workshops that seek to improve teachers’ ability to manage the classroom environment should be organized regularly to promote effective curriculum implementation.